Comparative study between 0.5% bupivacaine versus 0.5% ropivacaine in peribulbar anesthesia for cataract surgery - Neel Rana; Shruti M. Shah; Shrutika Parag Ved; Srushti R Shah; Patel Kushal Umeshkumar; Panchal Pratik Vijaybhai (Asian Journal of Medical Sciences, 2024)
Background: For intraocular surgery, the optimal local anesthetic agent must have a rapid onset of action and a sufficient duration of effect so as to enable a painless, motionless procedure without prolonging akinesia.